Implementation of IGG in IKMS Based on Entrepreneurship Programs in East Java - Ala'uddin, M.; Hakim, Lutfi; Najib, M.; Alimin, Alimin; Khalim, Abdul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
The main objective of this research is to gain explanative knowledge regarding the application of IGG in IKMS based on entrepreneurship programs in East Java. This multi-case study approach sets five Micro Waqf Banks and five Islamic Financial Institutions Recipient of Cash Waqf (LKS PWU) as research objects. The results of the study concluded that IGG in IKMS based on entrepreneurial programs was carried out through behavioral characteristics that showed the principles of shiddiq, amanah, fathonah and tabligh. The forms of behavior of the shiddiq principle at IGG include: (1) independence in the management and distribution process; (2) information accountability; (3) The characteristics of the behavior of the principle of trust are: (1) the selection of responsible customers; (2) fair and equal implementation of Standard Operational Procedures (SOP); (3) consistency of Group Endorsement Examination (UPK), Group Compulsory Training (PWK), Weekly Halaqoh (HALMI) and the establishment of Community Business Groups around Indonesian Islamic Boarding Schools (KUMPI); In the third principle, the behavioral characteristics of the fathonah principle include: (1) guarantees for providing capital for entrepreneurs; (2) stipulation of policy on ujrah payment as infaq for mauquf 'alaih; (3) stipulation of a policy for depositing a special waqf account; Finally, the tabligh principle is manifested in the following behavioral characteristics: (1) transparency of information and data to all customers; (2) leadership of member managers and customers; (3) implementation of mentoring programs to increase product marketing online; (4) transparency of financial reports, evaluation reports and ZISWAF allocations and (5) competent managers who are nimble in improving customer skills